The Politics of Agrarian Law in the Idea of Forming A Special Agrarian Court - Hana Maria Wiyanto; Yusriyadi; Ana Silviana (Journal of Law, Politic and Humanities, 2024)
The idea of a special agrarian court is really needed considering that up to now, various agrarian disputes or conflicts have not yet had a definite resolution. Agrarian is a field of science that has specificities, so it is not uncommon for problems regarding agrarian to be complex, because in one object the agrarian conflict may be related to several aspects simultaneously, for example criminal and civil aspects, not just administrative aspects. So we need a court institution with specialization in the agrarian field, consisting of competent experts in the agrarian field with the hope of being able to resolve agrarian conflicts and disputes that have not found a solution to date. Hoping that a special court in the agrarian sector exists, it will be able to function in providing justice, benefits and legal certainty for the community and The goal is to establish a fair and successful community that aligns with the ideals and goals.